2019
DOI: 10.1155/2019/2317976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Learning Methods Efficiency for Malicious and Benign System Calls Classification on the AWSCTD

Abstract: The increasing amount of malware and cyberattacks on a host level increases the need for a reliable anomaly-based host IDS (HIDS) that would be able to deal with zero-day attacks and would ensure low false alarm rate (FAR), which is critical for the detection of such activity. Deep learning methods such as convolutional neural networks (CNNs) and recurrent neural networks (RNNs) are considered to be highly suitable for solving data-driven security solutions. Therefore, it is necessary to perform the comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Combined models returned better accuracy results than separate usage of CNN and RNN models on speech, image, and infrared spectroscopy analysis. The aforementioned research encouraged us to use the linear ensemble with our previously tested [14] It can be seen that the LSTM-FCN, GRU-FCN, and FCN consist of a more complex structure in comparison with the AWSCTD-CNN, AWSCTD-CNN-LSTM, and AWSCTD-CNN-GRU models. This feature implies that those models can provide better results in intrusion detection, as suggested in Reference [16,17].…”
Section: Models and Configuration Parametersmentioning
confidence: 99%
See 4 more Smart Citations
“…Combined models returned better accuracy results than separate usage of CNN and RNN models on speech, image, and infrared spectroscopy analysis. The aforementioned research encouraged us to use the linear ensemble with our previously tested [14] It can be seen that the LSTM-FCN, GRU-FCN, and FCN consist of a more complex structure in comparison with the AWSCTD-CNN, AWSCTD-CNN-LSTM, and AWSCTD-CNN-GRU models. This feature implies that those models can provide better results in intrusion detection, as suggested in Reference [16,17].…”
Section: Models and Configuration Parametersmentioning
confidence: 99%
“…In our previous research conducted with the AWSCTD dataset, CNN, LSTM, and GRU methods were evaluated. The maximum achieved accuracy was equal to 94.5% and 99.3% for 100 and 1000 first system calls, respectively, with a simple CNN configuration [14]. In recent years, research on the combination of CNNs and RNNs into one model has shown promising results [72][73][74] and was applied from image recognition to Bitcoin price prediction tasks.…”
mentioning
confidence: 99%
See 3 more Smart Citations